Mobile based application for learning Italian language for UiTM level 1 students / Muhammad Taufiq Othman - Othman, Muhammad Taufiq (2016)
Mobile phone has become more important and already becoming as platform for people to gather knowledge and information. Mobile Based Assisted Learning is an application that acts as guideline and references to student who is taking Italian Language as their third language subject. Previously, Students only learn from class and assessment given from their lecturer. Most of the material are from books and notes that dull and bored. Students need to be motivated through interactive platform that can attract them to keep revising in order to memorize and understand the learning contents. Italian language has unique grammatical rules that hard to understand and remember. This project provide a convenient way which is through interactive elements such as audio, interactive interface and follow the syllabus of UiTM format for student to refer to the information anywhere and anytime they want. The contents cover only level 1 syllabus which is pronouns, masculine and feminine, indefinite articles and verbs. This research provides explanation for every lessons and formula for some grammatical rule that hard to remember. Besides, there are provided with quiz and exercise to enhance students’ knowledge during the learning process. Therefore, this research can become the solution to overcome these problems.